2020
DOI: 10.1056/nejmc2007575
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy and Antiphospholipid Antibodies in Patients with Covid-19

Abstract: Covid-19 CasesTo rapidly communicate information on the global clinical effort against Covid-19, the Journal has initiated a series of case reports that offer important teaching points or novel findings. The case reports should be viewed as observations rather than as recommendations for evaluation or treatment. In the interest of timeliness, these reports are evaluated by in-house editors, with peer review reserved for key points as needed. Coagulopathy and Antiphospholipid Antibodies in Patients with Covid-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
2,046
14
124

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,083 publications
(2,254 citation statements)
references
References 1 publication
70
2,046
14
124
Order By: Relevance
“…A recent study reported 3 cases with severe COVID-19 and cerebral infarction, one associated with bilateral limb ischemia, in the setting of elevated antiphospholipid antibodies. Whether antiphospholipid antibodies play a major role in pathophysiology of thrombosis associated with COVID-19 requires further investigation (35).…”
Section: Covid-19 and Hemostasis Parametersmentioning
confidence: 99%
“…A recent study reported 3 cases with severe COVID-19 and cerebral infarction, one associated with bilateral limb ischemia, in the setting of elevated antiphospholipid antibodies. Whether antiphospholipid antibodies play a major role in pathophysiology of thrombosis associated with COVID-19 requires further investigation (35).…”
Section: Covid-19 and Hemostasis Parametersmentioning
confidence: 99%
“…4 One case series of 3 patients with lower-extremity ischemia described an association of antiphospholipid antibodies (anti-cardiolipin immunoglobulin A [IgA], anti-beta-2-glycoprotein I IgA and IgG positive, lupus anticoagulant negative) and coagulopathy of COVID-19. 12 A recent study including 150 patients from ICUs across France showed a remarkably high rate of positive tests for lupus anticoagulant; 50 out of 57 patients who were tested for lupus anticoagulant (87.7%) to further evaluate an elevated aPTT tested positive. 13 Progression of coagulopathy to overt DIC, as indicated by an International Society on Thrombosis and Hemostasis (ISTH) DIC score of 5 points or higher, is seen in 71.4% of all non-survivors, compared with only 0.6% of survivors.…”
Section: ■ Laboratory Findingsmentioning
confidence: 99%
“…The lung injury is non-cardiogenic in nature and caused primarily by neutrophil-dependent and platelet-dependent damage to the endothelial and epithelial barriers of the lung, frequently caused by pneumonia [30]. A procoagulant effect with coagulopathy and anti-phospholipid antibodies has also recently been reported in patients with COVID-19 [31], associated with a poorer prognosis in patients with novel coronavirus pneumonia (NCP) [32]. Supportive measures in the management of ARDS have included attention to fluid balance, restrictive transfusion strategies, and minimization of sedatives and neuromuscular blocking agents, along with inhaled bronchodilators which have been shown to confer short term improvement without proven effect on survival [33].…”
Section: Introductionmentioning
confidence: 99%